Platelet Activation via Shear Stress Exposure Induces a Differing Pattern of Biomarkers of Activation versus Biochemical Agonists - Roka-Moiia, Yana; Walk, Ryan; Palomares, Daniel E.; Ammann, Kaitlyn R.; Dimasi, Annalisa; Italiano, Joseph E.; Sheriff, Jawaad; Bluestein, Danny; Slepian, Marvin J. (Thrombosis and Haemostasis, 2020)
Background Implantable cardiovascular therapeutic devices, while hemodynamically effective, remain limited by thrombosis. A driver of device-associated thrombosis is shear-mediated platelet activation (SMPA). Underlying mechanisms of SMPA, as well as useful biomarkers able to detect and discriminate mechanical versus biochemical platelet activation, are poorly defined. We hypothesized that SMPA induces a differing pattern of biomarkers compared with biochemical agonists.Methods Gel-filtered human platelets were subjected to mechanical activation via either uniform constant or dynamic shear; or to biochemical activation by adenosine diphosphate (ADP), thrombin receptor-activating peptide 6 (TRAP-6), thrombin, collagen, epinephrine, or arachidonic acid. Markers of platelet activation (P-selectin, integrin αIIbβ3 activation) and apoptosis (mitochondrial membrane potential, caspase 3 activation, and phosphatidylserine externalization [PSE]) were examined using flow cytometry. Platelet procoagulant activity was detected by chromogenic assay measuring thrombin generation. Contribution of platelet calcium flux in SMPA was tested employing calcium chelators, ethylenediaminetetraacetic acid (EDTA), and BAPTA-AM.Results Platelet exposure to continuous shear stress, but not biochemical agonists, resulted in a dramatic increase of PSE and procoagulant activity, while no integrin αIIbβ3 activation occurred, and P-selectin levels remained barely elevated. SMPA was associated with dissipation of mitochondrial membrane potential, but no caspase 3 activation was observed. Shear-mediated PSE was significantly decreased by chelation of extracellular calcium with EDTA, while intracellular calcium depletion with BAPTA-AM had no significant effect. In contrast, biochemical agonists ADP, TRAP-6, arachidonic acid, and thrombin were potent inducers of αIIbβ3 activation and/or P-selectin exposure. This differing pattern of biomarkers seen for SMPA for continuous uniform shear was replicated in platelets exposed to dynamic shear stress via circulation through a ventricular assist device-propelled circulatory loop.Conclusion Elevated shear stress, but not biochemical agonists, induces a differing pattern of platelet biomarkers—with enhanced PSE and thrombin generation on the platelet surface. This differential biomarker phenotype of SMPA offers the potential for early detection and discrimination from that mediated by biochemical agonists.
Keywords: shear-mediated platelet activation; shear stress; cardiovascular therapeutic device; phosphatidylserine externalization; biomarker